ANALYZING THE RELATIONSHIP BETWEEN FINANCIAL BALANCE AND FINANCIAL STABILITY: AN APPLIED STUDY ON COMMERCIAL BANKS LISTED IN THE IRAQ STOCK EXCHANGE - HIND DHEYAA ABDULRASOOL (Scholar Express Journals, 2025)
The purpose of the current research is to examine the impact of financial balance on the financial stability of commercial banks (Ashur Bank, Investment Bank, Sumer Bank, Bank of Baghdad, and Middle East Bank) in the Iraq Stock Exchange for the fiscal period (2014- 2023). By highlighting the reality and importance of financial balance in Iraq, the extent of financial services expansion can be determined by including banking categories and services that contribute to the expansion of investment projects in the country. Therefore, the current research primarily aimed to address a key problem formulated in the question: "To what extent does financial balance impact financial stability among commercial banks in the Iraq Stock Exchange?" The study used the Excel (SPSS v. 29) office suite to extract the best findings in order to evaluate and explain them. The study compiled numerous significant results, the most notable of which is that reaching financial stability depends on financial balance. A good financial balance serves to stabilize financial institutions, lower the risk of crises, and guard the national economy from unplanned changes.
Keywords: financial balance; financial stability; commercial banks